The Relationship between Problematic Mobile Use and Sleep Quality among Nursing Students: The Mediating Role of Perceived Stress - Sadoughi, Majid (Advances in Nursing & Midwifery, 2018)
Background and Aims: Excessive and problematic use of mobile phones could have several negative effects on different aspects of students’ lives. The current study aimed to explore the relationship between excessive mobile use and sleep quality among nursing students by considering the mediating role of perceived stress. Material & Methods: The present study was descriptive with a correlational design. One hundred and thirty-eight nursing students (103 females, 35 males) were randomly chosen through random sampling. The data collection instruments included Cell-Phone Over-Use Scale (COS), <a href="https://www.researchgate.net/profile/Patrick_Strollo/publication/23707561_Relationships_between_the_Pittsburgh_Sleep_Quality_Index_PSQI_Epworth_Sleepiness_Scale_ESS_clinicalpolysomnographic_measures_in_a_community_sample/links/0c960521bb4f001dbc000000.pdf">Pittsburgh Sleep Quality Index (PSQI), and Cohen’s Perceived Stress Scale. Pearson Product Moment Correlation, Independent Samples t Test, and Hierarchical Regression Analysis were run in SPSS (version 22) to analyze the data. Result: The mean of students’ age, mobile use, sleep quality, and perceived stress were 20.81±1.89, 52.17±14.70, 11.8±2.69, and 22.60±6.45, respectively. There was no statistically significant difference in terms of the aforementioned variables among male and female nursing students. The results of hierarchical regression analysis showed that mobile use in the first model can predict students’ sleep quality (β=.38). Upon entering the perceived stress to the equation, β of mobile use decreased, indicating the incomplete mediating role of perceived stress. Conclusion: Given the increasing use of mobile phones, it is highly important to examine their negative effects such as low sleep quality, high perceived stress, and their undesirable effects on students’ life. Hence, students’ awareness of negative effects of problematic mobile use could be raised via taking appropriate measures and making necessary interventions.